Evaluating the plasma interleukin-1 beta and interleukin-8 levels in patients with chronic obstructive pulmonary diseases following treatment with allogeneic mesenchymal stem cell derived from umbilical cord tissues and platelet rich plasma - Minh Trung, Do; Ngoc Bang, Dao; Phuong Ha, Le; Ba Thang, Ta; Van Mao, Can; Thi Bich Phuong, Le; Khac Hung, Dong (Vietnam Journal of Biotechnology, 2023)
Chronic obstructive pulmonary disease (COPD) is a common disease which negatively affects living quality and longevity of patients. Unfortunately, current COPD treatments are not radical. COPD is characterized by persistent neutrophil infiltrations mediated by inflammatory cytokines including interleukin (IL)-1β and IL-8 in the airway. Mesenchymal stem cells (MSCs) have been proven to suppress inflammation, modulate the immune system and can be regenerative. Allogeneic MSCs have been used to treat COPD patients across the world and produced positive clinical outcomes. In this study, we evaluated plasma IL-1β and IL-8 concentrations in 10 stage-D COPD patients before being transplanted with allogeneic MSCs derived from umbilical cord tissues (UC-MSCs) activated by platelet-rich plasma (PRP) and at 4 follow- ups (after 1, 3, 7, 12 months), as well as determined their associations with COPD clinical and sub-clinical parameters. Plasma IL-1β and IL-8 concentrations were measured using Multiplex Immunoassay. We found that plasma IL-8 levels were significantly reduced from 3.2 to 1.9 pg/ml after 12 months of treatment which is accompanied by the notable decrease in C-reactive protein (CRP). Exacerbation episodes were significantly decreased from 3 to 1. Plasma IL-1β levels were positively correlated with IL-8 levels and white blood cell (WBC) levels. Parallel measurements of plasma IL-1β and IL-8 may help assess the disease progression of COPD patients after the treatment with UC- MSCs and PRP. Blockage of IL-1β or IL-8 could be a valid strategy for the prevention and control of COPD.